Lack of Understanding of Cervical Cancer and Screening Is the Leading Barrier to Screening Uptake in Women at Midlife in Bangladesh: Population-Based Cross-Sectional Survey. (20th November 2015) - Islam, Rakibul M.; Bell, Robin J.; Billah, Baki; Hossain, Mohammad B.; Davis, Susan R.
Abstract: Background: Cervical cancer (CCa) is the second most common cancer among women in Bangladesh. The uptake of CCa screening was less than 10% in areas where screening has been offered, so we investigated the awareness of CCa and CCa screening, and factors associated with women's preparedness to be screened. Methods: A nationally representative, cross-sectional survey of women aged 30–59 years was conducted in 7 districts of the 7 divisions in Bangladesh, using a multistage cluster sampling technique. Factors associated with the awareness of CCa and screening uptake were investigated separately, using multivariable logistic regression. Results: On systematic questioning, 81.3% and 48.6% of the 1, 590 participants, whose mean age was 42.3 (±8.0) years, had ever heard of CCa and CCa screening, respectively. Having heard of CCa was associated with living in a rural area (adjusted odds ratio [OR]: 0.42; 95% confidence interval [CI]: 0.26–0.67), being 40–49 years old (OR: 1.59; 95% CI: 1.15–2.0), having no education (OR: 0.25; 95% CI: 0.16–0.38), and being obese (OR: 2.04; 95% CI: 1.23–3.36). Of the 773 women who had ever heard of CCa screening, 86% reported that they had not been screened because they had no symptoms and 37% did not know screening was needed. Only 8.3% had ever been screened. Having been screened was associated with being 40–49 years old (OR: 2.17; 95% CI: 1.19–3.94) and employed outside the home (OR: 3.83; 95% CI: 1.65–8.9), and inversely associated with rural dwelling (OR: 0.54; 95% CI: 0.30–0.98) and having no education (OR: 0.29; 95% CI: 0.10–0.85). Conclusion: Lack of awareness of CCa and of understanding of the concept of screening are the key barriers to screening uptake in women at midlife in Bangladesh. Targeted educational health programs are needed to increase screening in Bangladesh with the view to reducing mortality. Abstract : A nationally representative, cross-sectional survey of women aged 30–59 years in Bangladesh showed that 81.6% of women had heard of cervical cancer (CCa) but only 48.6% were aware of CCa screening. Only 8.3% had ever been screened. Lack of CCa awareness and of understanding of the concept of screening are the key barriers to screening uptake in this cohort.